Assessment of frailty in patients with advanced chronic kidney disease, and the role of microvesicles: A single-center study - Rocio Gimena Muñoz; Gemma Valera Arévalo; María del Mar Rodríguez San Pedro; María Pérez Fernández; Juan Arévalo Serrano; Sushrut S. Waikar; Rafael Ramírez-Chamond; Diego Rodríguez Puyol; Julia Carracedo; Patricia Martinez Miguel (PLoS ONE, 2025)
Background Frailty is a highly prevalent syndrome in patients with advanced age and chronic diseases, and it is associated with atherothrombotic pathologies, suggesting a procoagulant state in these patients. Circulating microvesicles (cMVs), are small phospholipid-rich vesicles, which have been shown to participate in atherothrombotic onset and progression. We aim to analyze frailty in patients with advanced chronic kidney disease (CKD), and to determine the role of microvesicles in this population. Materials and methods We conducted a prospective cohort study with 85 patients with advanced CKD. Our main objective was to evaluate frailty and its novel association with circulating microvesicles in advanced CKD. To define frailty, Fried’s five criteria were used and we obtained blood for cMVs analysis by flow cytometry. Results The prevalence of frailty in patients with advanced CKD was 27% (CI 95% 17-37%). We found that risk factors for frailty were age (OR 1.06; CI 95% to 1.11; p=0.027), type 2 diabetes mellitus (OR 5.77; CI 95% to 18.9; p=0.004) and hemoglobin (g/dL) (OR 0.63; CI 95% to 0.94; p=0.023). Total cMVs, platelet derived cMVs and endothelial derived cMVs were significantly higher in frail patients. In the predictive multivariable binary logistic regression model over frailty, three predictors explain 41% of the variability of frailty (Nagelkerke square R = 0.41; p <0.001) with the following contribution: T2DM (19%), total cMVs (14%) and hemoglobin (8%). Discussion Frailty is highly prevalent in patients with advanced CKD. Although we still do not know in depth the mechanisms involved in frailty, to our knowledge this is the first study that links cMVs and frailty in patients with advanced CKD. In our opinion it could be explored as a good biomarker or therapeutic target in advanced CKD.